Developing a typology of mentoring programmes for young people attending secondary school in the United Kingdom using qualitative methods. (May 2018) - Busse, Heide; Campbell, Rona; Kipping, Ruth
Abstract: Mentoring programmes are commonplace and delivered in a range of different ways in the United Kingdom and North America. To better understand the type of programmes available and to inform future evaluations, we developed a typology of formal mentoring programmes for young people in secondary schools in the United Kingdom. Telephone interviews with 23 programme managers from purposively sampled mentoring organisations were conducted and analysed using thematic and framework analysis. The typology was consulted on with five experts in mentoring. The final typology differentiates mentoring programmes by three overarching categories: type of mentor (older student, school staff, adult volunteer, paid adult), programme setting (school, community, online) and programme aim. The findings suggest that although mentoring programmes are heterogeneous, it is possible to group programmes into 'personal and developmental' and 'academic and employability' mentoring programmes and to differentiate between 12 overall mentoring models. The typology helps understand what is being delivered and how, which is a necessary precursor to any evaluation of health, educational, relational and social outcomes. Highlights: Formal mentoring programmes for young people are heterogeneous. Programmes can be distinguished by taking account of the type of mentor, programme setting and aim. Programmes can be grouped into 'personal and developmental' and 'academic and employability' programmes. Twelve distinct models of youth mentoring programmes have been identified in the United Kingdom.